Analisis Implementasi Pelayanan Antenatal Care di Puskesmas: Literatur Review - Amellia Sefti Lestari; Rizma Adlia Syakurah; Herawati Idris (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Efforts to reduce maternal and infant mortality rates in Indonesia continue to be a priority, with Antenatal Care (ANC) serving as a cornerstone of maternal healthcare. The Ministry of Health recommends a minimum of six ANC visits for pregnant women with uncomplicated pregnancies. However, challenges persist in the implementation of ANC services across community health centers (Puskesmas). These challenges include a lack of standardized protocols, limited digital literacy among healthcare providers, disparities between urban and rural healthcare access, insufficient personalized care, and socio-economic and cultural barriers. The government has recognized these issues and is taking steps to address them through initiatives such as the Digital Health Transformation Strategy (DHTS) 2.0, which aims to accelerate the digitalization of healthcare services. Additionally, the government is providing training for healthcare personnel, ensuring the integration of national healthcare systems, and offering financial support and regulatory frameworks to encourage the adoption of health technologies, including telemedicine, to improve service delivery, particularly in remote areas. These efforts are part of a broader strategy to enhance the quality and accessibility of maternal healthcare services and ultimately reduce maternal and infant mortality rates in Indonesia.